College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter P, Prerequisites - Section P.8 - Solving Basic Equations - P.8 Exercises - Page 60: 98



Work Step by Step

$a^{2}x+(a-1)=(a+1)x$ We move $x$ terms to one side: $a^{2}x-(a+1)x=-(a-1)$ Then we factor out $x$: $(a^{2}-(a+1))x=-a+1$ And simplify: $(a^{2}-a-1)x=-a+1$ Finally, we solve for $x$: $x=\frac{-a+1}{a^{2}-a-1}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.